First finding of a quarantine pest, Atherigona (Acritochaeta) orientalis Schiner (Diptera: Muscidae), in Korea - Suh, Sang Jae; Kwon, Yong Jung (Entomological research, 2016)
The invasive quarantine pest fly, Atherigona (Acritochaeta) orientalis Schiner, is observed for the first time in tomato greenhouses in Gyeongsangbuk‐do, Korea. The genus Atherigona Rondani is also newly added to Korean fauna. Allium tuberosum is listed as a new host crop for this species. Some morphological characteristics for accurate identification and host lists are given to provide plant quarantine information for pest management.